MECHANISMS OF ACTION OF TRADITIONAL HERBAL MEDICINES USED IN THE MANAGEMENT OF DIABETES MELLITUS: A REVIEW OF THE LITERATURE - Japhet, Mangoyi; Mlungisi, Ngcobo; Exnevia, Gomo (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The prevalence of diabetes mellitus is increasing rapidly in both developed and developing countries. There are various conventional medicines used for the management of the disease, but there is also increased interest in the use of traditional herbal medicines. Although the concepts of illness and diseases in traditional medicine may differ from conventional medicine the outcomes are similar. The antihyperglycemic effects of various herbal medicines prescribed by traditional healers in the management of diabetes mellitus have been proven scientifically using several in-vitro and in-vivo models as well as clinical studies in humans. Materials and methods: Literature search was done in several databases. Firstly, the search was conducted using the key terms: diabetes mellitus and traditional medicine, diabetes mellitus and herbs, diabetes mellitus and plants, traditional concepts of health and sickness and diabetes mellitus. After identifying the herbs or plants used in diabetes a search was then conducted by name of herb and efficacy in management of diabetes mellitus. Results: This review highlights the similarities and differences in mechanisms of action of various traditional herbal medicines and conventional medicines. The major observation is that, herbal medicines often have multiple mechanisms of action ideally making them combination therapies. The review further highlights the need to develop an algorithm of a minimum battery of in-vitro and animal studies that can provide solid evidence of the potential of traditional medicines as anti-diabetic treatments. Conclusion: Traditional herbal medicines often have multiple phytoconstituents and hence multiple mechanisms of action ideally making them combination therapies.